PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PASIEN DENGAN MEDIASI KEPUASAN PASIEN RUMAH SAKIT UMUM DAERAH MAS AMSYAR KASONGAN - Aditya Candra L. Awat, Natanael; Meitiana, Meitiana; Kristinae, Vivy; Giovanni, Jonathan (Penerbit Lafadz Jaya, 2025)
This study aims to analyze the effect of service quality on patient loyalty with mediation of patient satisfaction at Mas Amsyar Kasongan Regional General Hospital. This study used a quantitative design with a survey method of 96 patients selected by purposive sampling using the Lameshow formula. The questionnaire was distributed online and analyzed with Structural Equation Modeling (SEM) 4.0 to test the relationship between research variables. The results show that service quality influences patient satisfaction at Mas Amsyar Kasongan Regional General Hospital. Service quality influences patient satisfaction at Mas Amsyar Kasongan Regional General Hospital. Patient loyalty influences patient satisfaction at Mas Amsyar Kasongan Regional General Hospital. Patient satisfaction mediates the effect of service quality on patient loyalty at Mas Amsyar Kasongan Regional General Hospital.